Selecting SNP markers reflecting population origin for cacao (Theobroma cacao L.) germplasm identification - Osman A. Gutiérrez; Kathleen Martinez; Dapeng Zhang; Donald S. Livingstone; Chris J. Turnbull; Juan Carlos Motamayor (Beverage Plant Research)
Cacao is one of the most economically important agricultural commodities in the world, providing the principal ingredient for the global chocolate industry. Accurate genotype identification is essential for effective conservation and utilization of cacao germplasm. Here, we report the screening of 956 candidate SNPs, pre-selected from the 6 and 15K Theobroma cacao SNP Arrays using targeted Genotyping-by-Sequencing on 451 cacao germplasm accessions, representing ten known genetic groups from the tropical Americas. Based on call rate (No call rate < 5%), Minor Allele Frequency (MAF > 0.15) and Linkage Disequilibrium (LD ≤ 0.5), a total of 219 SNPs were selected. The efficacy of these SNP markers for population classification was compared with the previous SSR-based analysis in cacao. The population assignment results of the retained 420 cacao accessions was highly comparable with the SSR study. The matrix of genetic distance between SSR and SNP markers is highly correlated (r = 0.718; P < 0.001). These results demonstrated the consistency in using the present SNP markers for cacao germplasm identification. This is our pilot project for the development of SNP markers reflecting population origin for cacao germplasm identification. These SNP markers and the selected reference germplasm for different populations are suitable for use in cacao germplasm management and crop improvement, including genotype identification, seed gardens and nursery accreditation, and cocoa authentication. Effort is being continued with the emphasis on selecting SNP markers for the detection of sub-population structures in the primary gene pool of T. cacao.